“An Ancient System of Caste”: How the British Law against Caste Depends on Orientalism - Prakash Shah (Theatrum Historiae)
In 2010 the UK became the first jurisdiction in the West to enact a provision in anti-discrimination law based on caste. Parliamentarians justified the insertion of a provision against caste discrimination in the Equality Act 2010 on the assumption that a caste system exists in the UK’s Indian diaspora. While that merely gave a power to the Minister to implement the provision, an amendment to the Act made in 2013 made implementation obligatory. Indian community organisations had no real way of arguing against the provision. They were handicapped by the fact that if they resisted it they would be branded as complicit in caste discrimination – as has been alleged by parliamentarians backing the law – or practitioners of a form of apartheid. This article argues that the legislation is underpinned by dubious and insubstantial research. The absence of a credible research base meant that for the first time in the history of anti-discrimination law in the UK, parliament proceeded to legislate on the assumption that a problem exists. Equally troubling was the acceptance among proponents that an adequate conceptualization of a supposed problem, including defining caste, could be dealt with retrospectively, once legislation was in place. Further no case was made that a mechanism like the Equality Act is appropriate for caste discrimination. Legislators seemed largely ignorant of, or simply misrepresented, laws prevailing in South Asian countries. In parallel to the legislation and despite the lack of implementation as yet, the article also discusses how case law has proceeded to incorporate caste discrimination by reading it into the provision of the existing legislation. The effort of including caste in law, whether through legislation or case law presupposes and imports ideas of the caste system that rest on shaky foundations. The stereotype of the caste system goes back to Christian theological accounts of India, developed further in Orientalist accounts during the colonial period, and is incorporated in the social sciences today. These ideas led to the notions that the Indian social structure is morally corrupt and racist, notions that continue to strongly condition contemporary thinking on caste as reflected in the development in UK law.